Marvel and Legendary Pictures in the Attention Economy: Insights from the Innovation and Transformation of Media and Advertising Strategies for the Chinese Film and Television Industry - Xiao, Zexin (Transactions on Economics, Business and Management Research, 2024)
The purpose of this study is to summarize the innovative and transformational methods of Marvel and Legendary Pictures in their own media and advertising strategies in the era of the attention economy. This research project found that Marvel’s media strategy innovation and transformation in the era of the attention economy include a cross-media narrative system, the use of social media platforms to cultivate fan culture, and the use of new media for marketing. Marvel’s innovation and transformation in advertising strategy include cross-media promotion, adjusting promotional policies for each region in the global market, using trailers and Easter eggs for promotion, using events for marketing, using big data for user profiling analysis for targeted advertising, developing IP resources, and conducting integrated marketing. The innovation and changes made by Legendary Pictures in its media and advertising strategies during the era of the attention economy include cross-disciplinary development, localized advertising strategies, joint production and distribution of films with mainstream film companies, and planning and layout of IP resources. Media and advertising strategies are important means for film and television companies to attract audience attention in the era of the eye economy. Marvel and Legendary Pictures have both made outstanding innovations and transformations. This research project discusses how these innovations and transformations are specifically carried out. This research project reviews literature related to the research topic, analyzes its relevant content, and extracts keywords for summarization.